Do We Become More Prosocial as We Age, and if So, Why?. (June 2020) - Mayr, Ulrich; Freund, Alexandra M.
Older adults contribute—through charitable donations or volunteering—more to the common good than younger adults, an age difference that has profound society-level implications. Yet the reasons for this difference are not well understood. Evidence suggests that a purely altruistic concern for the common good is a major motivation for prosocial behavior and that this concern increases across adulthood. We argue that this finding, and prosocial behavior in general, is better understood using a value-based decision framework than through traditional dual-process accounts. Following the value-based decision approach, we derive specific hypotheses about life-span changes in motivation or resources as factors that explain why older adults show an increased concern for the well-being of other people.